Предмет: Алгебра,
автор: Аноним
Найти значение выражения 4(3х-5у)+6(х-у)
СРОЧНО ПЖ
Ответы
Автор ответа:
3
Сначала упростим данное выражение:
4(3х-5у)+6(х-у)=12х-20у+6х-6у=18х-26у
При х=1/2, у=1/13 получаем: 18*1/2-26*1/13=9-2=7
4(3х-5у)+6(х-у)=12х-20у+6х-6у=18х-26у
При х=1/2, у=1/13 получаем: 18*1/2-26*1/13=9-2=7
Автор ответа:
0
4(3х-5у)+6(х-у)=12х-20у+6х+6у=18х-26у.
Похожие вопросы
Предмет: Право,
автор: thesmokeman
Предмет: Алгебра,
автор: andreale
Предмет: Математика,
автор: novikovamargarita324
Предмет: Математика,
автор: Famir
Предмет: География,
автор: nastyakassina94